HUBUNGAN ANTARA DUKUNGAN KELUARGA DAN PERILAKU SELF-MANAGEMENT DENGAN TINGKAT STRES MENJALANI DIET PADA PENDERITA DIABETES MELITUS TIPE 2 DI KELURAHAN NAMBANGAN LOR KECAMATAN MANGUHARJO KOTA MADIUN - Amaliathus Sholikhah; Retno Widiarini; Pipid Ari Wibowo (J-KESMAS: Jurnal Kesehatan Masyarakat, 2020)
Puskesmas Manguharjo is a health center in Madiun City where the number of diabetes sufferers has increased every year with a total of 2,186 cases in 2019, spread across 4 urban villages, one of which is in the Nambangan Lor sub-district in 2019, there were 109 cases of which their blood sugar was checked. The purpose of this study was to determine the relationship between family support and self-management behavior with the stress level of undergoing a diet in type 2 diabetes mellitus sufferers in Nambangan Lor Village, Manguharjo City, Madiun District. This type of research used a cross-sectional study design. The number of samples needed is 86 people with the sampling technique used is simple random sampling using the Chi_Square test. Based on bivariate analysis, variable family support p = 0.021 and self-management behavior p = 0.006 proved to be associated with stress levels of dieting in people with type 2 diabetes mellitus in Nambangan Lor Village, Manguharjo District, Madiun City. The results showed that most of the type 2 DM sufferers had poor family support as many as 50 people, had good self-management behavior as many as 46 people, and most had moderate stress levels as many as 33 people. Researchers provide suggestions, namely to increase family support for people with diabetes mellitus